Diallel Analysis of Callus Induction and Green-Plant Regeneration in Rice Anther Culture - Quimio, C.A.; Zapata, F.J. (Wiley, 1990)
Low efficiencies of callus induction and green‐plant regeneration have limited the application of anther culture in breeding programs. This study was conducted to determine the inheritance of callus induction and plant regeneration in rice (Oryza sativa L.) anther culture. Sixteen genotypes derived from a four‐parent diallel mating set of two Japonica cultivars (Taipei 309 and Taipei 177) and two indica cultivars (IR36 and Basmati 370) were evaluated for their callus induction and plant regeneration abilities. For callus induction, the effects of genotype and genotype ✕ medium interaction were significant (P < 0.05). Similarly, genotype and abscisic acid (ABA) level were found to be significant (P < 0.05) for green‐plant production. The japonica cultivars generally had a higher percent callus induction and plant regeneration, and number of calli producing green plants than did the indica cultivars. Similar modes of inheritance were observed for both characters. Combining ability analysis demonstrated the predominance of additive gene effects in the control of both characters with the japonica cultivars having higher combining ability for green‐plant regeneration. Reciprocal effects were not significant (P > 0.05), suggesting the absence of maternal control on the characters. Further analysis showed gene action to be partially dominant with high response being highly recessive and controlled by a few genes. There were no indications of inter‐allelic interaction.